A triple-blind randomized clinical trial of different associations between dexamethasone and non-steroids anti-inflammatories for preemptive action in third molar extractions - Momesso, Gustavo Antonio Correa [UNESP]; Grossi-Oliveira, Gustavo Augusto [UNESP]; Silva, William Phillip Pereira [UNESP]; Akira, Renan [UNESP]; Chiba, Fernando [UNESP]; Polo, Tárik Ocon Braga [UNESP]; de Lima Neto, Tiburtino José [UNESP]; Rios, Bárbara Ribeiro [UNESP]; Bassi, Ana Paula Farnezi [UNESP]; Sumida, Doris Hissako [UNESP]; Han, Michael; Miloro, Michael; et al. (Springer Nature, 2021)
The aim of this study is to evaluate the preemptive analgesic effects of dexamethasone (DEX) alone or combined with non-steroidal anti-inflammatory drugs (NSAIDs) in third molar surgeries. The subjects were divided into five groups (n = 20 teeth/group); subjects received only 8 mg of dexamethasone 1 h before the surgical procedure (DEX group), or in combination with etodolac (DEX + ETO), ketorolac (DEX + KET), ibuprofen (DEX + IBU), loxoprofen (DEX + LOX). Paracetamol 750 mg was provided as the number of rescue analgesics (NRA). Salivary PGE2 expression was measured preoperatively and at 48 h. Edema and Maximum mouth opening (MMO) were measured postoperatively at 48 h and 7 days. A visual analog scale (VAS) was performed postoperatively at 6, 12, 24, 48, 72 h, and 7 days. Salivary expression of PGE2 showed a decrease only for the DEX group. Edema and MMO and NRA consumption showed no significant differences among the groups (P > 0.05). The VAS showed a significantly lower pain perception at 6 h after the surgery for the DEX + ETO and DEX + KET groups (P < 0.05). The combination of DEX and NSAIDS should be considered for preemptive acute postsurgical pain management in third molar surgery. In some drug associations such as dexamethasone 8 mg + NSAIDS (ETO and KET) in the pre-operative time, only a few rescue analgesics are necessary.